2021
DOI: 10.21037/tlcr-21-937
|View full text |Cite
|
Sign up to set email alerts
|

Carinal resection and reconstruction with complete pulmonary parenchyma preservation: a single-institution analysis of 36 cases

Abstract: Background: Carinal resection, performed in only a few high-volume centers, remains one of the most complicated and technically demanding surgeries. Few studies have examined the outcomes of carinal resection and reconstruction with complete pulmonary parenchyma preservation.Methods: Patients who underwent isolated carinal resection and reconstruction at the Shanghai Chest Hospital between 2006 and 2020 were retrospectively reviewed. Clinicopathological, perioperative, and follow-up outcomes were analyzed.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
1
3
0
2
Order By: Relevance
“…Therefore, the feasibility of VATS for carina reconstruction may require more investigation in a larger cohort. Finally, the incidence of the anastomotic fistula was 10.81% (4 of 37 patients) in our study, similar to that reported by previous research that ranged from 8.3% to as high as 20% 5,6,8,13 . However, all of the anastomotic fistula led to prolonged air leaks, pneumonia, acute respiratory distress syndrome, and even death in our study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, the feasibility of VATS for carina reconstruction may require more investigation in a larger cohort. Finally, the incidence of the anastomotic fistula was 10.81% (4 of 37 patients) in our study, similar to that reported by previous research that ranged from 8.3% to as high as 20% 5,6,8,13 . However, all of the anastomotic fistula led to prolonged air leaks, pneumonia, acute respiratory distress syndrome, and even death in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the incidence of the anastomotic fistula was 10.81% (4 of 37 patients) in our study, similar to that reported by previous research that ranged from 8.3% to as high as 20%. 5 , 6 , 8 , 13 However, all of the anastomotic fistula led to prolonged air leaks, pneumonia, acute respiratory distress syndrome, and even death in our study. Therefore, this common, but severe complication of carina reconstruction should be taken seriously and dealt with properly to achieve better perioperative outcomes.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Die Deckung der Bronchialanastomose durch einen gestielten, effektiv perfundierten Gewebelappen, z. B. aus Thymusrestgewebe, Interkostalmuskel oder Latissimus-dorsi-Lappen, wird von den meisten Autoren empfohlen [15,32,38,43]. Die Durchtrennung von Trachea und Bronchien führt, trotz Präservation der oberflächlichen Gefäßversorgung, zu einer passageren Ischämie der Bronchialschleimhaut distal der Anastomose.…”
Section: Deckung Der Anastomoseunclassified